Respuesta :
y = 6x...so sub in 6x for y in the other equation
x + 2y = -39
x + 2(6x) = -39
x + 12x = -39
13x = -39
x = -39/13
x = - 3
y = 6x
y = 6(-3)
y = -18
solution is (-3,-18)
======================
5x + 2y = 7
-5x + 4y = 5
-----------------add
6y = 12
y = 12/6
y = 2
5x + 2y = 7
5x + 2(2) = 7
5x + 4 = 7
5x = 7 - 4
5x = 3
x = 3/5
solution is (3/5,2)
========================
y = 4x - 9
y = x - 3
sub one y in for the other
4x - 9 = x - 3
4x - x = -3 + 9
3x = 6
x = 6/3
x = 2
y = x - 3
y = 2 - 3
y = -1
solution is (2,-1)
x + 2y = -39
x + 2(6x) = -39
x + 12x = -39
13x = -39
x = -39/13
x = - 3
y = 6x
y = 6(-3)
y = -18
solution is (-3,-18)
======================
5x + 2y = 7
-5x + 4y = 5
-----------------add
6y = 12
y = 12/6
y = 2
5x + 2y = 7
5x + 2(2) = 7
5x + 4 = 7
5x = 7 - 4
5x = 3
x = 3/5
solution is (3/5,2)
========================
y = 4x - 9
y = x - 3
sub one y in for the other
4x - 9 = x - 3
4x - x = -3 + 9
3x = 6
x = 6/3
x = 2
y = x - 3
y = 2 - 3
y = -1
solution is (2,-1)